Desperate undertaking - Davis, Lindsey (Davis, Lindsey. Flavia Albia mystery, 2022)
"In Lindsey Davis's next book in the beloved Flavia Albia Series, Desperate Undertaking, a mad killer (or killers!) is strewing bodies around in the most gruesome of manners and, true to form, it is up to Flavia Albia to determine what is really going on and stop this bacchanal of death. In the first century, under Domitian's reign, strange and brutal goings on are nothing new in Rome. Flavia Albia, daughter of Marcus Didius Falco, has taken over her father's business as a private informer but she tries to shy away from the brutal, the complicated, and the political - because nothing good comes of any of them. Unfortunately, she's not very good at turning them down. This time a commission shows up on her doorstep - someone is staging brutal murders in some of the most beautiful buildings in Rome, each staging different. So far, the only clue was the phrase that one survivor managed to croak, "The undertaker did it..." With little to go on and bodies starting to pile up, Albia has to unravel the strangest mystery of her career in short order if she's to stop this dismaying orgy of murder"--